A new method for synthesis of N,N-diethyl-m-methylbenzamide - Pham Duc Thinh; Phan Dinh Chau; Do Duc Anh; Do Ba Quyet; Vu Binh Duong (Revista Cubana de Medicina Militar)
Introduction: N, N-diethyl-m-methylbenzamide or N, N-diethyl-m-toluamide (DEET), is well known as an insect repellent. In addition, it is used to improve the dermal and transdermal delivery of many drugs. Objectives: To present a feasible procedure to synthesize DEET from m-toluic acid and diethylamine. Methods: The m-toluic acid was activated with 1,1'-carbonyl-diimidazole, to obtain the intermediate product 1- (m-toluoyl) imidazole that continues to react with diethylamine, to produce DEET. In this way, the factors affecting the synthesis of N, N-diethyl-m-toluamide are improved. Results: DEET was obtained through an optimal procedure. The by-products of the reaction are soluble in water; they are easily removed by the liquid-liquid extraction method with water and dichloromethane. Most of the DEET obtained has high purity. The yields were 94 to 95 %. Conclusions: An improved route has been provided for a simple and efficient synthesis of DEET from m-toluic acid and diethylamine in the presence of 1,1'-carbonyl-diimidazole. The synthesis procedure was carried out in one-pot, and the isolation of DEET was achieved by liquid-liquid extraction. The total procedure time was significantly reduced. This synthesis method is easily scalable and industrially feasible.